Joint Resposibility System As The Key Success Of Women's Cooperative Setia Bhakti Indonesian East Java Woman - Iwang Suwangsih; Fendy Suhariadi; Dwi Ratmawati; Sayyida Sayyida; Nuzulul Fatimah (LPPPIPublishing, 2022)
The aim of this study is to describe about the key success of women's cooperative “Setia Bhakti Wanita (SBW) Jawa Timur” which used a joint responsibility system to manage the cooperative’s business so becomes a big cooperative in East Java Indonesia. It also becomes a learning place for the joint liability system for other cooperatives. This research is a descriptive qualitative research. The outcomes of this study found that the key to the success of the SBW women's cooperative in managing the cooperative business is consistently implementing a joint responsibility system, do monitoring and mentoring, using joint liability as an organizational culture, giving education and training to member, knowledge sharing between members.